Study on the Attractiveness Factors of Online Courses - Jia-Xuan Han; Min-Yuan Ma (MDPI AG, 2019)
With the rapid development of online courses, digital learning has become a global trend. In this context, this study analyzed the high intake population of online courses for online affective cognition, and explored what the user’s attraction factors for online courses are. The key factors that affect consumers’ usage of online courses and the weights of impact relations are presented, aiming to provide guidance for future improvement of online courses. This study was conducted through the evaluation grid method of Miryoku engineering. In order to make the charm factors more accurate and representative, this study summarized the charm elements using the Kawakita Jiro (KJ) method, and then quantified the factors in the form of a questionnaire. Through the statistical analysis of the questionnaire and quantification theory type I, the correlation between the charm feeling and the online course as well as the weight of each item (original evaluation item) and category (specific evaluation item) were calculated. Through the research and discussion on the charm factors of online teaching, the results analyzed and integrated in this paper could give more substantive suggestions and help to the education industry.